An outranking approach based on interval type-2 fuzzy sets to evaluate preparedness and response ability of non-governmental humanitarian relief organizations - Celik, Erkan; Gumus, Alev Taskin (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
After a disaster occurs, national and international non-governmental humanitarian relief organizations (NGOs), as well as the governmental humanitarian relief organizations (GOs), are involved in carrying out the humanitarian relief operations because of insufficiency in recourses such as lack of equipment and human resources. GOs and NGOs play a crucial role in preparedness and response to natural disasters, especially when available resources of them are not enough. The preparedness and response ability of GOs and NGOs aim to minimize the losses and number of affected people. Therefore, the preparedness and response ability of NGOs are becoming more important to support governmental relief activities. In this paper, a hybrid approach, that consists of interval type-2 fuzzy sets, AHP and PROMETHEE, is proposed to evaluate emergency preparedness and response ability performances of NGOs. The proposed hybrid approach is applied to NGOs in Turkey to evaluate their performances, and is conducted in three phases: (1) determination of critical success factors (CSFs) of humanitarian relief logistics management operations, (2) application of interval type-2 fuzzy AHP for obtaining importance weights of CSFs and (3) application of PROMETHEE based on interval type-2 fuzzy sets to evaluate preparedness and response abilities of NGOs. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: Non-governmental humanitarian relief organizations; Humanitarian relief logistics; Type-2 fuzzy sets; AHP; PROMETHEE; CRITICAL SUCCESS FACTORS; ANALYTIC HIERARCHY PROCESS; FACILITY LOCATION; CUSTOMER SATISFACTION; DECISION-MAKING; MCDM METHOD; EMERGENCY; LOGISTICS; Computer Science; Engineering